The role of the tumour microenvironment components in cancer cell behaviour and drug response - Senthebane, Dimakatso Alice (Department of Integrative Biomedical Sciences (IBMS), 2023)
Cancer is a public health burden which continues to cause many deaths and an economic burden worldwide. New and improved ways of thinking about anti-cancer drug design and development are needed now and in future. Recent reports demonstrate the key role played by the tumour microenvironment (TME) in tumour progression and the development of drug resistance. This study investigated the interactions between cancer cells and the stroma within the TME, specifically fibroblasts, mesenchymal stem cells (MSC), cancer stem cells (CSCs) as well as the extracellular matrix (ECM), with the goal to develop an in vitro model that mimics solid tumours in terms of cellular characteristics and drug response. Mesenchymal stem cells were investigated as potential sources of cancer-associated fibroblasts (CAFs) in solid tumours. The expression of CAFs markers, α-SMA and vimentin, increased significantly in MSCs co-cultured with oesophageal and breast cancer cells indicating conversion of MSCs into cell-like CAFs. WHCO1 (oesophageal) and MDA MB 231 (breast) cancer cells co-cultured with MSCs survived paclitaxel and cisplatin treatments better than cancer cells alone. To assess the prognostic value of CSCs, the expression and malignant behaviour of CSC markers were also examined in clinicopathologically-confirmed oesophageal cancer biopsies and in vitro. Oesophageal cancer biopsies stained strongly for the cancer stem cell markers, CD44 and ALDH1A1, demonstrating the presence of CSCs in these tumours. FACS-isolated side population cells exhibited high levels of cancer stem cell markers, self-renewal markers and drug resistance proteins and were associated with increased drug resistance versus cancer cells. In order to measure how ECM proteins affect oesophageal cancer cell response to chemotherapeutic drugs, 3D cell-derived ECMs was used as a model. The analysis of ECM proteins using qRT-PCR in oesophageal cancer biopsies showed that collagens, fibronectin, and laminins were overexpressed in tumour tissue compared with adjacent normal tissues. The culture of cancer cells on decellularised ECMs reduced the effect of drugs on cancer cells compared to those plated on plastic (control). The reduction of the effects of drugs was associated with significant activation of survival signalling pathways. Knockdown of collagen and fibronectin with siRNA combined with drugs resulted in increased sensitivity of cancer cells to drugs and lower colony formation and cancer cell migration. Lastly, this study utilized multi-cell tumour spheroids (MCTS) from WHCO1 and MDA MB 231 cells co-cultured with WI38 and CT1 fibroblasts to mimic tumour cell-stromal cell interactions as observed within the in vivo tumour microenvironment. The data show that spheroids were more resistant to drugs than monolayer cultures of the same cells. MCTS displayed characteristics similar to in vivo tumours in terms of response to drugs. Associated with these findings were increased levels of CSCs in MCTS compared to monolayer. This study demonstrated that MSCs are a possible source of ‘CAFs' in vivo and can support cancer cell growth. This study also demonstrated the presence of CSCs in tumours and that the targeting of these cells can shrink tumours and prevent potential metastasis and relapse of tumours. This study revealed that ECM proteins play major roles in the response of cancer cells to chemotherapy and suggest that targeting ECM proteins, especially type I collagen and fibronectin, can be an effective therapeutic strategy against chemoresistant tumours. MCTS, as shown in this study, is a valuable tool for the evaluation of the therapeutic effect of drugs. Overall, this study demonstrates the critical role played by the tumour microenvironment in tumour growth and metastasis and provides new insights into cancer treatment.